Effects of physical activity and physical exercise, as a motor experience in children and Recibido: Enero, 2021 Aceptado: Mayo, 2021 Dirección para correspondencia: Carolina Soldan Solís Programa Magíster en Ejercicio Físico y Salud, Universidad San Sebastián, Puerto Montt, Chile c.soldansolis@gmail.com adolescents with autism spectrum disorder; a systematic review (Revista horizonte, 2022)
Objective: To decide the effects produced by physical activity and physical exercise, whether in individual or collective practice, in children and teenagers with autistic spectrum disorders (ASDs). Methods: The systematic review implied in a detailed analysis about scientific articles oriented in the investigation of the effects in children and teenager ASDs doing exercise. The research was carried out in the databases of Pubmed, academic google, and Ebsco, including articles of the last 10 years; the interventions had to involve the practice of physical exercise planned with specific objectives in children and teenagers ASDs, whether in individual or collective practices. Results: Effects were identified in three aspects; cognitive, communicational and motor skills. Observing improvements in socialization and stereotyped behavior, through the performance of planned recreational motor activities, with the presence of sensory stimulations, motivating an environment conducive to learning. Conclusion: Physical exercise had a direct positive effect on children and teenagers with autism spectrum disorder, evidencing improvements in quality of life and well-being, generating spaces for interrelations with people of the same age, environment, and family.